2002
DOI: 10.1021/jf010908o
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antioxidant Capacity of Sulfated Polysaccharides from the Edible Marine Brown Seaweed Fucus vesiculosus

Abstract: Fucus vesiculosus was sequentially extracted with water at 22 degrees C (fraction 1 (F1)) and 60 degrees C (F2), and with 0.1 M HCl (F3) and 2 M KOH (F4) at 37 degrees C. Soluble fractions (42.3% yield) were composed of neutral sugars (18.9-48 g/100 g), uronic acids (8.8-52.8 g/100 g), sulfate (2.4-11.5 g/100 g), small amounts of protein (< 1-6.1 g/100 g), and nondialyzable polyphenols (0.1-2.7 g/100 g). The main neutral sugars were fucose, glucose, galactose, and xylose. Infrared (IR) spectra of the fractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
257
0
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 547 publications
(289 citation statements)
references
References 22 publications
22
257
0
10
Order By: Relevance
“…Saccharolytic species of bacteria, such as Lactobacilli spp., take part in the breakdown of complex carbohydrates (Salyers, 1979). Fucoidan is soluble in water making it a rapidly fermentable carbohydrate source (Rupé rez et al, 2002), and Lactobacillus spp. have been reported to ferment a number of monosaccharides including L-fucose (Salyers et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Saccharolytic species of bacteria, such as Lactobacilli spp., take part in the breakdown of complex carbohydrates (Salyers, 1979). Fucoidan is soluble in water making it a rapidly fermentable carbohydrate source (Rupé rez et al, 2002), and Lactobacillus spp. have been reported to ferment a number of monosaccharides including L-fucose (Salyers et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors reported important ABTS radical scavenging capacity activity of solvent extracts from algae (Ayyad et al, 2011;Balboa et al, 2013). The reducing power was high both for the phenolic rich extracts and for fucoidan rich extracts; the reducing capacity of crude polysaccharides and fucoidan from brown algae is well known (Rupérez et al, 2002;Chattopadhyay et al, 2010). The activity in emulsion was higher for the extracts with higher phenolic content and lower for the algal extracts.…”
Section: In Vitro Chemical Antioxidant Assaysmentioning
confidence: 99%
“…The mechanism by which these compounds may reduce protein digestibility is through hydrogen-binding and/or oxidation of proteins and amino acids rendering them unavailable to proteolytic enzyme hydrolysis and subsequent intestinal absorption. Several recent studies have reported the TPC of algalderived ingredients including seaweeds (Wong and Cheung 2001;Rupérez et al 2002;Heffernan et al 2014)a n d microalgae (Duval et al 2000;Li et al 2007;Goh et al 2010;H a j i m a h m o o d ie ta l .2010;C u s t ó d i oe ta l .2012; Goiris et al 2012). However, comparison of TPC between feed ingredients is difficult because of the high level of heterogeneity of the broad classification of phenolic compounds; thus, it is only possible to get relative equivalents with the standards used (Julkunen-Tiitto 1985).…”
Section: −1mentioning
confidence: 99%